Factors Affecting Mothers Regarding the Completeness of Immunisation in Infants Aged 0-12 Months in the Kamawen Auxiliary Health Centre Working Area - Ketut Senenawati; Tut Rayani Aksohini Wijayanti (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Immunization is among the most efficacious health strategies for avoiding infectious illnesses in babies and diminishing child morbidity and mortality. Despite the extensive implementation of routine immunisation programmes, immunization coverage among infants aged 0–12 months remains suboptimal and is affected by numerous factors, especially maternal characteristics. Maternal factors significantly influence adherence to the immunization regimen throughout early infancy. This study seeks to examine the determinants affecting immunization coverage in infants aged 0–12 months within the jurisdiction of the Kamawen Auxiliary Health Centre. The research employs an observational analytical design with a cross-sectional methodology. The study sample comprises women with infants aged 0–12 months, selected using purposive sampling. Data were gathered via structured interviews employing questionnaires and by verifying newborn immunization status through the Mother and Child Health (MCH) book. Data analysis was conducted univariately and bivariately employing the chi-square test, with a significance threshold of p < 0.05. The findings indicated that the majority of newborns had attained full immunization in accordance with the established schedule. Bivariate analysis revealed a substantial correlation between maternal education level and age and the completion of baby immunization. Mothers with elevated educational attainment and of advanced reproductive age were inclined to produce infants with full immunization status. The characteristics of maternal education and age are substantially correlated with the completion of immunization for infants aged 0–12 months. These findings underscore the necessity of enhancing immunization teaching and counseling customized to maternal factors to elevate immunization coverage at the primary health care level.